PENGARUH PENERAPAN STANDAR AKUNTANSI PEMERINTAHAN, KOMPETENSI APARATUR PEMERINTAH DAERAH DAN GOOD GOVERNANCE TERHADAP KUALITAS LAPORAN KEUANGAN DAERAH (Studi Empiris Pada Dinas Kota Palangka Raya) - Raibbatol Advia; Agus Satrya Wibowo; M. Ichsan Diarsyad (Balance: Media Informasi Akuntansi dan Keuangan, 2022)
The effect of applying government accounting standards, competence human resources, and good governance on quality of regional financial reports (Empirical Study at the Palangka Raya City). Thesis, Department of Accounting, Faculty of Economics and Business. This study aims to provide an empirical explanation of applying government accounting standards, competence human resources, and good governance affect the quality of financial reports. The study had a population of 18 Palangka Raya City Offices. This study uses primary data in the form of a questionnaire with a purposive sampling method, which is the sample obtained is 72 people. The data analysis technique in this research is causality analysis, validity and reliability of the instrument test and multiple linear analysis. The results of this study indicate that the government accounting standards, competence human resources, and good governance affect the quality of financial reports. Furthermore, it is suggested for further researchers to develop a sample and is expected to be able to test it with other variables outside the research.